Desperate Journeys. (2nd May 2019) - Adams, Jeff
Abstract: At a time of endemic xenophobia some artists have attempted to resist this trend by depicting its damaging consequences, revealing the inequalities that fuel its disfigurement of human relations and result in mass human displacement. Paul Dash's recent paintings of refugees attempting dangerous and degrading sea crossings are the main subject of this article, and these works are discussed in the context of his negative educational experiences as a child, and his salvation through painting in the sanctuary of his school's art room. This school experience and the trajectory of his artistic career are contextualised by the current marginalisation of the arts in the curriculum and the increasing scarcity of critical and creative approaches to education.